2011
DOI: 10.1002/pro.603
|View full text |Cite
|
Sign up to set email alerts
|

Probing the self‐association, intermolecular contacts, and folding propensity of amelogenin

Abstract: Amelogenins are an intrinsically disordered protein family that plays a major role in the development of tooth enamel, one of the most highly mineralized materials in nature. Monomeric porcine amelogenin possesses random coil and residual secondary structures, but it is not known which sequence regions would be conformationally attractive to potential enamel matrix targets such as other amelogenins (self-assembly), other matrix proteins, cell surfaces, or biominerals. To address this further, we investigated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…40 Based on the PPII propensity scale for individual amino acid residues, we previously reported that PPII is the dominant structure in the central region of amelogenin 33 and our solvent engineering studies confirmed that the Pro, Gln central domain is resistant to folding. 40 The rigidity in the central region and flexibility at the N- and C- termini may have important functional significance for amelogenin in vivo . 40 …”
Section: Amelogenin and Its Targetssupporting
confidence: 61%
See 2 more Smart Citations
“…40 Based on the PPII propensity scale for individual amino acid residues, we previously reported that PPII is the dominant structure in the central region of amelogenin 33 and our solvent engineering studies confirmed that the Pro, Gln central domain is resistant to folding. 40 The rigidity in the central region and flexibility at the N- and C- termini may have important functional significance for amelogenin in vivo . 40 …”
Section: Amelogenin and Its Targetssupporting
confidence: 61%
“…40 The rigidity in the central region and flexibility at the N- and C- termini may have important functional significance for amelogenin in vivo . 40 …”
Section: Amelogenin and Its Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals DMP1 4.0 CD, DLS, FTIR, SAXS (Gericke et al, 2010;He et al, 2003aHe et al, , 2003b DPP 2.8 CD, NMR, SAXS (Cross et al, 2005;Evans et al, 1994;Fujisawa & Kuboki, 1998;George & Hao, 2005;He et al, 2005b;Lee et al, 1977) BSP 4.1 CD, NMR, SAXS (Fisher et al, 2001;Tye et al, 2003Tye et al, , 2005Wuttke et al, 2001) OPN 4.4 CD, NMR, FTIR (Fisher et al, 2001;Gorski et al, 1995) amelogenin 6.6 CD, NMR (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011;Shaw et al, 2008) statherin 8.0 CD, NMR (Long et al, 2001;Naganagowda et al, 1998;Raj et al, 1992) lithostathine 5.7 CD (Gerbaud et al, 2000) Haliotis rufescens AP7 5.2 CD, NMR (Kim et al, 2004(Kim et al, , 2006aMichenfelder et al, 2003;Wustman et al, 2004) Atrina rigita Asprich 2.7-3.5 CD, NMR (Collino et al, 2006;Delak et al, 2009aDelak et al, , 2008Kim et al, 2008;Ndao et al, 2010) Procambrus clarkii CAP-1 3.9 CD (Inoue et al, 2007) Strongylocentrotus purpuratus SM50 10.8 CD, NMR (Xu & Evans, 1999;Zhang et al, 2000) PM27 8.1 CD, NMR Danio rerio Stm 4.1 CD, gel filtration (Kaplon et al, 2008(Kaplon et al, , 2009 Table 1. IDPs involved in biomineralization of calcium carbonate and phosphate for which a disordered structure has been confirmed...…”
Section: Protein Pi Methods Referencementioning
confidence: 99%
“…There is no well-defined, continuous region with an ordered structure, but some residual secondary structure was observed. In addition, amelogenin exists in at least two conformations (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011). Amelogenin can interact with other important proteins engaged in enamel formation (Bartlett et al, 2006).…”
Section: Enamel Proteinsmentioning
confidence: 99%